2011
DOI: 10.1159/000322977
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Probiotic Bifidobacterium and Galacto-Oligosaccharide in Patients with Ulcerative Colitis: A Randomized Controlled Study

Abstract: Background/Aim: In previous studies, we described the beneficial effects of bifidobacteria-fermented milk in patients with ulcerative colitis (UC). Here, we examined the effects of a live Bifidobacterium breve strain Yakult, a probiotic contained in bifidobacteria-fermented milk, and galacto-oligosaccharide (GOS) as synbiotics in UC patients. Methods: Forty-one patients with mild to moderate UC were assigned to two groups; one group was treated with the synbiotics and the other was not (control). The treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(96 citation statements)
references
References 41 publications
1
92
0
3
Order By: Relevance
“…Synbiotics consisted from Bifidobacterium breve and galacto-oligosaccharide (38) or Bifidobacterium longum and psyllium (39) also ameliorated colitis or patient's qualityof-life. However, only a few clinical trials have suggested beneficial effects of prebiotics in UC patients.…”
Section: Effects Of a Fiber-rich Fermented Food On The Human Fecal MImentioning
confidence: 99%
“…Synbiotics consisted from Bifidobacterium breve and galacto-oligosaccharide (38) or Bifidobacterium longum and psyllium (39) also ameliorated colitis or patient's qualityof-life. However, only a few clinical trials have suggested beneficial effects of prebiotics in UC patients.…”
Section: Effects Of a Fiber-rich Fermented Food On The Human Fecal MImentioning
confidence: 99%
“…11) Moreover, GOS and bifidobacteria are also given in a combined treatment referred to as a synbiotic, with the aim of enhancing the effect of exogenous bifidobacteria. [15][16][17][18] In this context, synbiotic administration of live Bifidobacterium breve strain Yakult and GOS to patients with ulcerative colitis has improved their clinical condition. 18) Although the above-mentioned GOS effects on endogenous and exogenous bifidobacteria have been well documented, several questions remain unraveled.…”
mentioning
confidence: 99%
“…[15][16][17][18] In this context, synbiotic administration of live Bifidobacterium breve strain Yakult and GOS to patients with ulcerative colitis has improved their clinical condition. 18) Although the above-mentioned GOS effects on endogenous and exogenous bifidobacteria have been well documented, several questions remain unraveled. For one, it is not known why the response to GOS consumption is subject to considerable individual variation.…”
mentioning
confidence: 99%
“…El estudio de Ishikawa y colaboradores en Japón mostró el éxito de esta conducta en el mantenimiento de la remisión, con una reducción significativa de las exacerbaciones, y posibles efectos preventivos en recaídas con el uso de un suplemento de leche fermentada con bifidobacteria (simbiótico) 100 mL/día durante 1 año en 41 pacientes. Hallazgo reafirmado en un nuevo estudio realizado por el mismo autor en 2011, con evidencia de mejoría clínica, colonoscópica y disminución de niveles de mieloperoxidasa en 21 pacientes (p <0,05) (42,43). En el mismo país, el estudio de Fujimori con 31 pacientes comparó Bifidobacterium longum 2 x 10 9 UFC y 8 g de psyllium (prebiótico) con simbiótico únicamente y encontró mayor impacto con manejo combinado, con remisión mantenida durante las 4 semanas de tratamiento (p=0,03) (44).…”
Section: Colitis Ulcerativaunclassified